English Teaching at Secondary Education: An Innovative Proposal - Carvajal-Portuguez, Zayra Elisa (2013)
An innovative proposal is developed for teaching English at secondary education, specifically in the operative curriculum.  That is, the curriculum that takes place between the teacher and their students in the classroom.  Such proposal aims to reach the objectives that have already been assigned to schools at the secondary education.  These schools have been given the power to shape, train, evaluate and instruct students, so that secondary education students really acquire the English language in such a way that they will have the capacity to communicate through the use of this language.  This proposal takes into account the necessary instruments for teaching English; including assessment and its indicators to determine the level of proficiency each student has as well as the activities planned to develop the different skills in order to acquire this language.  These instruments offer as significant curricular contributions for the implementation of this proposal by English teachers since it provides them with the necessary information to determine the student’s level of English proficiency and the activities these teenagers can successfully perform in order to improve their level.  It is relevant to highlight that those instruments develop four English language skills: listening, speaking, reading, and writing. As it is established in the English Syllabus by the Ministry of Public Education in Costa Rica.